Altered resting-state functional connectivity in emotion-processing brain regions in adults who were born very preterm. Issue 14 (15th August 2016) - Papini, C.; White, T. P.; Montagna, A.; Brittain, P. J.; Froudist-Walsh, S.; Kroll, J.; Karolis, V.; Simonelli, A.; Williams, S. C.; Murray, R. M.; Nosarti, C.
Abstract : Background: Very preterm birth (VPT; <32 weeks of gestation) has been associated with impairments in emotion regulation, social competence and communicative skills. However, the neuroanatomical mechanisms underlying such impairments have not been systematically studied. Here we investigated the functional integrity of the amygdala connectivity network in relation to the ability to recognize emotions from facial expressions in VPT adults. Method: Thirty-six VPT-born adults and 38 age-matched controls were scanned at rest in a 3-T MRI scanner. Resting-state functional connectivity (rs-fc) was assessed with SPM8. A seed-based analysis focusing on three amygdalar subregions (centro-medial/latero-basal/superficial) was performed. Participants' ability to recognize emotions was assessed using dynamic stimuli of human faces expressing six emotions at different intensities with the Emotion Recognition Task (ERT). Results: VPT individuals compared to controls showed reduced rs-fc between the superficial subregion of the left amygdala, and the right posterior cingulate cortex ( p = 0.017) and the left precuneus ( p = 0.002). The VPT group further showed elevated rs-fc between the left superficial amygdala and the superior temporal sulcus ( p = 0.008). Performance on the ERT showed that the VPT group was less able than controls to recognize anger at low levels of intensity. Anger scores were significantly associated with rs-fc between the superficial amygdala and the posterior cingulate cortex in controls but not in VPT individuals. Conclusions: These findings suggest that alterations in rs-fc between the amygdala, parietal and temporal cortices could represent the mechanism linking VPT birth and deficits in emotion processing.